2013
DOI: 10.1016/j.ejphar.2012.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Opioid mediated activity and expression of mu and delta opioid receptors in isolated human term non-labouring myometrium

Abstract: TitleOpioid mediated activity and expression of mu and delta opioid receptors in isolated human term non-laboring myometrium AbstractThe existence of opioid receptors in mammalian myometrial tissue is now widely accepted. Previously enkephalin degrading enzymes have been shown to be elevated in pregnant rat uterus and a met-enkephalin analogue has been shown to alter spontaneous contractility of rat myometrium. Here we have undertaken studies to determine the effects of met-enkephalin on in vitro human myomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Zhu and Pintar (1998) have found μ and κ opioid receptors in the endometrium and myometrium of pregnant mice. Furthermore, μ and δ opioid receptors were identified in woman myometrium (Fanning et al, 2013). The present study demonstrated in vitro the time-depended changes in the basal expression of genes for opioid receptors in the porcine endometrial explants.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Zhu and Pintar (1998) have found μ and κ opioid receptors in the endometrium and myometrium of pregnant mice. Furthermore, μ and δ opioid receptors were identified in woman myometrium (Fanning et al, 2013). The present study demonstrated in vitro the time-depended changes in the basal expression of genes for opioid receptors in the porcine endometrial explants.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, it has been demonstrated that EOPs may be implicated in the regulation of several processes in the uterus such as: its contractility, secretory activity, local immunomodulation, cell proliferation and apoptosis (Petit et al, 1993;Cemerikic et al, 1994;Adjroud, 1995;Környei et al, 1997;Zoumakis et al, 1997;Chatzaki et al, 2001;Fanning et al, 2013). Variable data concerning the modulation of uterine muscle contractility by opioids have been reported for different species and reproductive stages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations